Economics of endoparasitic control in the Ethiopian highlands - Ngategize, P.K.; Ezaz, Z.; Brokken, R.F. (Research Inst. for Animal Husbandry, 1990)
Presents an economic evaluation of nutritional and anthelmintic control measures to endoparasitism using experimental data. Reviews the biological and economic effects of endoparasitism and analyzes the economic returns to different endoparasitic treatments. Identifies current endoparasitic control strategies and areas for further research.